Assessment of the Effect of Fruit (Apple) and Plain Yoghurt Consumption on Plaque pH - Peyvand Moeiny; Sahar Sayahpour; Farhad Raofie; Alireza Aminikhah; Mohamad Javad Kharazifard (Mashhad University of Medical Sciences, 2017)
Introduction: Nowadays, thanks to improvements in fruit yoghurt tastes, more tendencies are seen in their consumption especially among children. Therefore, their cariogenicity evaluation as healthy snacks is important. The goal of this study was the assessment of the consumption effect of two kinds of Iranian fruit (apple) and plain yoghurts on dental plaque PH. Methods: In this experimental study, 10 healthy dentistry students were selected upon inclusion criteria. Plaque pH in the certain areas of the mouth was measured by microelectrode and digital pH meter. PH was measured at the baseline and intervals of 2, 5, 7, 10, 15, 20, 30, 40, 50 and 60 minutes after eating test products: fruit yoghurt (apple) and plain Yoghurt. For positive control group, just the baseline PH and at intervals of 2 and 5 min after swishing with 10% sucrose solutions were recorded. The results were analyzed using repeated measures ANOVA. Results: Lowest pH was obtained after fruit yoghurt consumption followed by plain yoghurt and %10 sucrose solution and the plaque PH difference was significant (P=0.05). Furthermore, time duration which remained below the critical pH was longer after consuming fruit yoghurt. Conclusion: Both kinds of yoghurts were considered cariogenic since plaque pH drop below critical points. Average of plaque pH after consuming fruit yoghurt was significantly lower in almost all the time intervals